Une formulation mixte-hybride naturelle robuste pour la modélisation des coques courbes isotropes - Ayad, Rezak (European Journal of Computational Mechanics, 2005)
This work deals with a natural hybrid-mixed variational formulation for the linear analysis of isotropic and homogeneous curved shells. The model NHMiSP (Natural Hybrid- Mixed with Shear Projection) is based on the 3D-degenerated solid approach. Il can be used to simulate arbitrary shells presenting a warpage. The membrane model is based on the Pian’s natural approach. The bending model is formulated using the classical Hellinger- Reissner principle. Two bending equilibrium equations are satisfied at the variational level, allowing to get a partially hybrid transverse shear model. The shear locking problem is avoided using the ANS method (Assumed Natural Strains). The derived finite element model (4-node quadrilateral) is validated using some standard shell tests.